1998
DOI: 10.1149/1.1838921
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electropolymerized Polyindole: Application in the Construction of a Solid‐State, Ion‐Selective Electrode

Abstract: The characterization of polyindole made by anodic electropolymerization of indole monomer in dichioromethane is reported based on scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The results on SEM show that the granules in the polymer film are arranged in an ordered manner. The domain of the nuclei in the film made under potentiostatic condition is much smaller as compared to the domain of the nucleation in the polymer film made under potentiodynamic condition. The DSC data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
37
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 2 publications
17
37
0
Order By: Relevance
“…Similar to the results in the literature, 43 the steady-state cyclic voltammograms represented broad anodic and cathodic peaks. The peak current densities were proportional to the scan rates (insert of Figures 3A, B), indicating the reversible redox behavior of the polymer.…”
Section: Electrochemistry Of Ppvk Filmssupporting
confidence: 89%
“…Similar to the results in the literature, 43 the steady-state cyclic voltammograms represented broad anodic and cathodic peaks. The peak current densities were proportional to the scan rates (insert of Figures 3A, B), indicating the reversible redox behavior of the polymer.…”
Section: Electrochemistry Of Ppvk Filmssupporting
confidence: 89%
“…Polyindole (PIn) though not as soughtafter as PANI or PPy for use as modified electrode due to its relatively low electrical conductivity, yet there are studies concerning the electropolymerization, characterization and use of this polymer as sensors and as anticorrosion coatings because of its good thermal and environmental stability [13][14][15][16][17][18]. In our study reported here therefore, we demonstrate the use of polyindole electrosynthesised from aqueous medium as a matrix for dispersion of metallic particles.…”
Section: Introductionmentioning
confidence: 77%
“…On the other hand, polyindole synthesized under potentiodynamic condition shows regular distribution of polymer domain and interstices with doped electrolyte. 5 The oxidation potential of carbazole is larger (Ͼ1.2 V versus Ag/AgCl), whereas the oxidation potential of indole is Ͻ1.0 V versus Ag/AgCl.…”
Section: Physical and Electrochemical Characterization Of Polycarbazomentioning
confidence: 98%
“…4,5 The platinum surface was polished with alumina slurry to a mirror finish, followed by drying under a nitrogen stream. The electrochemical polymerization of polycarbazole was carried out in CH 2 ) acetate in the same buffer.…”
Section: Electrochemical Synthesismentioning
confidence: 99%